SOCIAL MEDIA AND SOCIAL RELATIONSHIPS: A CASE STUDY IN KURDISTAN SOCIETY - GHAREB, Mazen; KARIM, Hawraman; SALIH, Shvan; HASSAN, Hiwa (Applied Computer Science, 2018)
These days, Social Media which is includes (Facebook, Instagram, Twitter, Linkedin) is an extremely well known social correspondence media. Individuals use Social Media to express their musings, thoughts, sonnets, and distresses on them. In the period of data superhighway, greater part of the young people are not sharing their challenges, issues, irregularity, powerlessness and disappointment with their folks in Kurdistan of Iraq. Be that as it may, they share with their companions on Social Media. Hence, their companions are making remarks, giving havens and affections to them. Because of absence of instruction and encounters on innovation, gatekeepers in Kurdistan don't know about the correspondences and addictions on social Medias. In this manner, there are producing holes in social relationships in the community. In this paper, a review has based and finding the effect of social media on personal and community relationships. Calculation dissects the practices of youngsters' by gathering data from a survey. Guardians and educators conclusions are additionally viewed as about the exercises of understudies on home and foundations. Here, age cutoff points of focused adolescents are somewhere in the range of 16 and 60. From this investigation, powerless connection amongst guardians and their adolescent youngsters have been taken note. The significant issue was that teenagers are investing more energy on social media and guardians need them to the table amid contemplate time and educational time.